2014
DOI: 10.3390/ijerph110505382
|View full text |Cite
|
Sign up to set email alerts
|

Range-Finding Risk Assessment of Inhalation Exposure to Nanodiamonds in a Laboratory Environment

Abstract: This study considers fundamental methods in occupational risk assessment of exposure to airborne engineered nanomaterials. We discuss characterization of particle emissions, exposure assessment, hazard assessment with in vitro studies, and risk range characterization using calculated inhaled doses and dose-response translated to humans from in vitro studies. Here, the methods were utilized to assess workers’ risk range of inhalation exposure to nanodiamonds (NDs) during handling and sieving of ND powder. NDs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…While the present study has shown, especially the two-and three-box layouts predicted well the concentration levels in a well-controlled environment, the next step is to test the model performance by comparing modelled exposure levels with measured exposure levels in different environments. A successful comparison requires exposure studies, where contextual information is described well, and that concentrations are measured from multiple locations (see, e.g., occupational exposure studies by Jensen et al [29], Koponen et al [42], Mølgaard et al [22], Koivisto et al [25,[43][44][45], and Fonseca et al [46,47]). In addition, chamber studies will be carried out to characterise the significance of source strength measurements and the dispersion factor.…”
Section: Discussionmentioning
confidence: 99%
“…While the present study has shown, especially the two-and three-box layouts predicted well the concentration levels in a well-controlled environment, the next step is to test the model performance by comparing modelled exposure levels with measured exposure levels in different environments. A successful comparison requires exposure studies, where contextual information is described well, and that concentrations are measured from multiple locations (see, e.g., occupational exposure studies by Jensen et al [29], Koponen et al [42], Mølgaard et al [22], Koivisto et al [25,[43][44][45], and Fonseca et al [46,47]). In addition, chamber studies will be carried out to characterise the significance of source strength measurements and the dispersion factor.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting end-product materials from chemical synthesis [23]; batch collection by industrial cyclone [24]; emptying and tipping powder materials from bucket to bucket [25]; scooping spilt materials off a table [25]; opening a furnace and transferring materials to vials [6]; manually loading and unloading trays [6]; dumping materials into a mixing tank [6]; detaching and removing CNTs from growth substrate using a razor blade [26]; sieving powders with a vibratory sieve shaker [27,28] Physical & chemical synthesis Gas-phase production of metal-based nanoparticles [29]; flame spray pyrolysis technique (FSP) [30,31]; induced coupled plasma with electric atomizer [32,33]; reaction collection [23]; electric arc reaction [34]; hot-wall reaction [19]; combustion reaction [35]; chemical vapor deposition (CVD) [26,[36][37][38][39]; water-assisted CVD [40] Weighing & mixing…”
Section: Collecting and Sorting During Enm Productionsmentioning
confidence: 99%
“…Spraying and filtration of CNT solutions [37]; spraying solution onto a bulk absorbent [6]; changing a spray dryer drum [6]; spraying a suspension [9]; flame-spraying for surface coating and modification [50]; sonicating materials with different surface coatings in a hood [6]; sonication in an unventilated enclosure [7]; pelletizing and bagging products in a warehouse [51]; purification and functionalization [47] integrating MWCNT powder in coatings, dispersions, and plastics [52] [53], Al2O3 [53], CeO2 [53], iron oxides [6], Mn [6], Ag [6,54], Co [6], Si [19]; Carbonaceous: carbon black [23], CNT [26], SWCNT [25,40,55], MWCNT [6,28,37,47], carbon nanofibers (CNFs) [6,48], carbon nanopearls [6], nano diamond [27], carbon nanodiscs/carbon nanocones [28], nanoscale graphene platelets [56].…”
Section: Collecting and Sorting During Enm Productionsmentioning
confidence: 99%
“…Nanoparticle emissions from industrial processes are receiving increasing attention in the literature in recent years (Demou, Peter, & Hellweg, 2008;Pfefferkorn et al, 2010;Curwin & Bertke, 2011;Gandra, Miranda, Vilaça, Velhinho, & Teixeira, 2011;Koivisto et al, 2012;Van Broekhuizen, 2012;Gómez, Irusta, Balas, & Santamaria, 2013;Fonseca et al, 2014;Gomez et al, 2014;Voliotis et al, 2014;Koivisto et al, 2014). These works focus on different types of processes, and reveal that nanoparticle emissions and subsequent exposures may reach up to particle number concentrations of 1 Â 10 6 parts cm À 3 such as the cases of firing processes where the painting and glazing of ceramics occur (Voliotis et al, 2014), as well as during and welding/soldering (Gómez et al, 2013).…”
Section: Introductionmentioning
confidence: 98%